Census of State and Federal Adult Correctional Facilities, 2000 ([Verlag nicht ermittelbar], 2004)
This census is the sixth enumeration of state adult correctional institutions and the third of federal institutions sponsored by the Bureau of Justice Statistics and conducted by the Bureau of the Census. Earlier censuses were completed in 1974 (ICPSR 7811), 1979 (ICPSR 7852), 1984 (ICPSR 8444), 1990 (ICPSR 9908), and 1995 (ICPSR 6953). For each facility, information was provided on physical security, age, functions, capacity, court orders for specific conditions, one-day counts and average populations, race/ethnicity of inmates, inmate work assignments, inmate deaths, special inmate counts, assaults, and incidents caused by inmates.